Reptiles de la reserva de usos múltiples Caleta de los Loros, Río Negro, Argentina - Vega, Laura Estela (1994)
A list of reptiles from Caleta de los Loros Reserve including their habitat association is given. In order to carry out censues and collection of specimenes, three surveys wich lasted 10 days each, were made in the study area. The resulting list contains 16 species: 1 tortoise, 8 lizards, 1 amphisbaenian and 6 snakes. The highest percentages of habitat associations were obtained for the monte (56%) and sand dunes (50%).